The Effect of Debt to Equity Ratio, Current Ratio, Total Assets Turnover, Sales Growth, and Firm Size Toward Profitability of Property Companies Listed on the Indonesia Stock Exchange - Jhonson; Yanuar Dananjaya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The purpose of this study was to determine the effect of Debt to Equity Ratio, Current ratio, Total Assets Turnover, Sales Growth, and Firm Size toward profitability. The population in this research is all property and real estate companies listed on the Indonesia Stock Exchange in the period 2019 - 2023. This research uses quantitative methods. The sample selection technique used in this research is the purposive sampling method and by using the specified criteria, 58 companies were obtained as research samples. The analysis technique in this research uses multiple linear regression analysis. The results showed that partially, debt to equity ratio, total assets turnover, and sales growth have positive and significant effects on profitability. Meanwhile, current ratio and firm size don't have a significant effect toward profitability. The simultaneous result showed that all independent variables have a significant effect toward profitability of property companies listed on the Indonesia Stock Exchange.